The management and maintenance of sewage treatment / Mohd Zulkifly Musa - Musa, Mohd Zulkifly (Faculty of Architecture, Planning and Surveying, 2008)
Sewage is the mainly liquid waste containing some solids produced by humans which typically consists of washing water, faeces, urine, laundry waste and other material which goes down drains and toilets from households and industry. It is one type of wastewater, and is a major actual or potential source of pollution especially in urban areas. Sewage services exist to manage sewage by collection, treatment and recycling or safe disposal into the environment. Sewage is created by residences, institutions, and commercial and industrial establishments. It can be treated close to where it is created (in septic tanks or on site package plants and other aerobic treatment systems), or collected and transported via a network of pipes and pump stations to a municipal treatment plant. Sewage collection and treatment is typically subject to local, state and federal regulations and standards (regulation and controls). Industrial sources of wastewater often require specialized treatment processes. Sewage is treated to remove or alter contaminants in order to minimize the impact of discharging wastewater into the environment. Beside that, sewage needs to treat in order to avoid water pollution. Water pollution not only gives effect to the aquatic habitat but also to the human.